COPING SEKSUAL BERBASIS PESANTREN PADA WARGA BINAAN DI RUMAH TAHANAN NEGARA (RUTAN) KLAS II B BATURAJA - Muhammad Arif Indra Nugraha; M Musrin (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2018)
For every normal human being and still productive age of sexual necessity is a basic need that is very necessary, so that if this requirement can not be fulfilled it will lead to deviant acts such as homosexual, masturbation, masturbation and other deviations. The problem in this research is how to coping to the assisted citizens in an effort to overcome the pressure because they can not channel their sexual desire in the State Detention Unit (RUTAN) Class II B Baturaja ?, what activities are done in pesantren in assisting sexual coping on the assisted citizens State Detention House (RUTAN) Class II B Baturaja? and how the pesantrenbased sexual coping of the assisted citizens at the State Detention Unit (RUTAN) Class II B Baturaja. The purpose of this research is to know the sexual coping of the assisted citizens who can not channel their sexual desire and the activities of the assisted people in pesantren, and how the pesantren-based sexual coping on the targeted citizens. This research was conducted at State Detention Station (RUTAN) Class II B Baturaja. The type of data used in this study is the type of qualitative data, data sources in this study were taken from primary data and secondary data. Research subjects in this study were the assisted citizens. Data collection techniques include interview method, observation method, documentation method. Data analysis techniques include data reduction, data presentation, data verification or conclusion drawing. From the results of this study obtained that the coping of assisted citizens in an effort to overcome sexual desire is; listening to the voice of the wife from the phone / Wartelpas, chatting with friends in Rutan, lying while imagining his wife, looking at his wife's photos, there also passes time undergoing the period of prisoner sexual desire is by itself not into their mind anymore, and there are citizens built if the desire sexually arises he immediately takes the ablution water and prepares to perform the prayer. Activities undertaken by the assisted people in the pesantren include: studying prayers 5 times, learning to pray the body, adzan, listening to lectures ustadz, studying and fasting. Sexual copies bebasis pesantren conducted by citizens built by the State Detainees (RUTAN) Class II B Baturaja among other methods that are performed by the assisted citizens during the period of detention by following the pesantren activities; pray 5 Time, fast, listen to ustadz lectures, share prayer, and dhikr. The process of pesantren-based sexual coping on the assisted people is by applying what has been taught in pesantren activities in everyday life such as praying, recitation and dhikr in their room, if the desire arises they immediately take ablution water and prepare to pray.